Skin Autofluorescence Is Associated with Endothelial Dysfunction in Uremic Subjects on Hemodialysis - Wang, Chun-Cheng (PLoS One, 2016)
BACKGROUND: Elevated levels of advanced glycation end products (AGEs) within tissues may contribute to endothelial dysfunction, an early indicator of atherosclerosis. We aimed to investigate whether levels of skin AGEs could be a useful marker to predict endothelial dysfunction in uremic subjects on hemodialysis. METHODS AND RESULTS: One hundred and nineteen uremic patients on hemodialysis and 57 control subjects with moderate-to-high cardiovascular risk factors and without chronic kidney disease (CKD) were enrolled. We used ultrasound to measure flow-mediated vasodilation (FMD). An AGE reader measured skin autoflurorescence (AF). We then compared differences in FMD and skin AF values between the two groups. The uremic subjects had significantly higher levels of skin AF (3.47±0.76 AU vs. 2.21±0.45 arbitrary units; P<0.01) and significantly lower levels of FMD (4.79%±1.88% vs. 7.19%±2.17%; P<0.01) than the non-CKD subjects. After adjusting for all potential covariates, we found that skin AF level independently predicted FMD in both the hemodialysis and the non-CKD groups. In the hemodialysis group, skin AF ≥ 3.05 arbitrary units predicted abnormal FMD at a sensitivity of 87.9% and a specificity of 78.6% (P<0.01). CONCLUSIONS: Skin AF could be a useful marker to predict endothelial dysfunction in uremic subjects on hemodialysis.